The Fate Of The Day: The War of America, Fort Ticonderoga to Charleston, 1777-1780 : the war for America, Fort Ticonderoga to Charleston, 1777-1780 - Atkinson, Rick (New York : Crown, 2025)
"In the second volume of the landmark American Revolution trilogy by the Pulitzer Prize-winning and #1 New York Times bestselling author of The British Are Coming, George Washington's army fights on the knife edge between victory and defeat"-- Provided by publisher.
Prologue: France, February-April 1777 -- The march of annihilation : Fort Ticonderoga, New York, July-August 1777 -- This cursed, cut-up land : New York, July-August 1777 -- Fellows willing to go to Heaven : Little Neshaminy Creek, Pennsylvania, August 1777 -- Thine arrows stick fast in me : Oriskany, New York, and Bennington, Vermont, August 1777 -- A barbarous business in a barbarous country : Brandywine, Pennsylvania, September 1777 -- These are dreadful times : Philadelphia and Paoli, Pennsylvania, September 1777 -- Born under a fiery planet : Germantown, Pennsylvania, October 1777 -- To risk all upon one rash stroke : Saratoga, New York, September 1777 -- How art thou fallen : Saratoga, New York, October 1777 -- The elements in flames : Philadelphia, October-December 1777 -- The King's War : London, November 1777-February 1778 -- Blessed be he that expects nothing : Paris, December 1777-February 1778 -- The vortex of small fortunes : Valley Forge, Pennsylvania, January-June 1778 -- I would rather lose the crown : London and Portsmouth, England, April-June 1778 -- The French flag in all its glory : Paris and the English Channel, March-July 1778 -- Flying from a shadow : Monmouth Court House, New Jersey, June 1778 -- Fortune is a fickle jade : New York and Newport, Rhode Island, July-August 1778 -- A star and a stripe from the rebel flag : New York and Savannah, Georgia, October 1778-February 1779 -- The uncertainty of human prospects : Philadelphia, December 1778-February 1779 -- A Summons to Queens House : London, January-July 1779 -- I detest that sort of war : Hampton Roads, Virginia, and Stony Point, New York, March-July 1779 -- The valley of bones : The American Frontier, June-August 1779 -- Everything is now at stake : British Home Waters, July-September 1779 -- The greatest event that has happened : Savannah, Georgia, September-October 1779 -- Eternity is nearer every day : Morristown, New Jersey, December 1779-February 1780 -- She stoops to conquer : Charleston, South Carolina, February-June 1780 -- Epilogue: England and America, 1780.
new book 2025 fall.
Includes bibliographical references and index.
Keywords: United States -- History -- Revolution, 1775-1783 -- Campaigns